A research on quality of life score (QOLS) of patients with trigeminal neuralgia (TN). Issue 5 (September 2019) - Luo, Yejiao; He, Mingjie; Li, Chenjun; Yang, Hongya
Abstract: Background: To evaluate the clinic effect of treatment of trigeminal neuralgia (TN). Methods: The current study aims to develop a multiple-scale characteristics quality of life (QOL) for patients with TN. After interview, the individual questionnaire was acquired. indicating the QOL has a good responsiveness and surveying effects of the dynamic state of health on TN patients. Conclusion: It is feasible to form multiple-scale characteristics QOL for patients with TN.